Production of Newsprint Grade Paper from a Mixture of Mechanical Pulp from Eucalyptus hybrid and Soda Semi-chemical Pulp from Bagasse - Guha, S. R. D.; Singh, Man Mohan; Bhola, P. P.; Mathur, G. M.; Sharma, Y. K.; Aggarwal, G. C. (Indian Forester, 1970)
Laboratory as well as pilot plant trials have been carried out on the production of newsprint grade paper from a mixture of mechanical pulp from Eucalyptus hybrid and soda semi-chemical pulp from bagasse. The results show that the newsprint produced in this manner compares very favourably with imported newsprint and Indian newsprint.